2019
DOI: 10.1155/2019/2472964
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and Biodegradable Electrospun Nanofibrous Membranes Loaded with Grape Seed Extract for Wound Dressing Application

Abstract: The development of nanofibrous membranes with tunable wettability, degradation, and biocompatibility is highly keen for biomedical applications, including drug delivery and wound dressing. In this study, biocompatible and biodegradable nanofibrous membranes with antioxidant properties were successfully prepared by the electrospinning technique. The membranes were developed using polylactic acid (PLA) and polyethylene oxide (PEO) as the matrix, with the addition of grape seed extract (GSE), a rich source of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 53 publications
5
55
0
Order By: Relevance
“…This degradation comprised approximately 60% of the initial weight. The shown behaviour is in agreement with other authors who reported similar wide thermal degradation processes for other natural extracts such as rosemary extract [52], Chimonanthus praecox extract [91], and grape seeds extract [54].…”
Section: Thermogravimetric Analysissupporting
confidence: 93%
See 4 more Smart Citations
“…This degradation comprised approximately 60% of the initial weight. The shown behaviour is in agreement with other authors who reported similar wide thermal degradation processes for other natural extracts such as rosemary extract [52], Chimonanthus praecox extract [91], and grape seeds extract [54].…”
Section: Thermogravimetric Analysissupporting
confidence: 93%
“…This behaviour was more evident at high AVE loading, showing a decrease in T 1% of approximately 21, 40 and 55% for 5, 10 and 20 wt%, respectively, which was associated with the initial thermal degradation of AVE present in the polymer formulations. Locilento et al found a similar behaviour with decreasing thermal stability of the resulted electrospun nanofibers upon encapsulation of grape seeds extract, which was attributed to the dissolution/dispersion of the bioactive compound before encapsulation [54]. However, a minor increase in the temperature of maximum degradation of PEO/AVE nanofibers was observed with the addition of AVE, showing no significant differences occurred (p > 0.05) with the increase in AVE content (Table 1).…”
Section: Thermogravimetric Analysismentioning
confidence: 68%
See 3 more Smart Citations